2021
DOI: 10.2147/idr.s321915
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Indexes of Liver and Kidney Injury Markers Predict Severity in COVID-19 Patients

Abstract: Background SARS-CoV-2 can damage not only the lungs but also the liver and kidney. Most critically ill patients with coronavirus disease 2019 (COVID-19) have liver and kidney dysfunction. We aim to investigate the levels of liver and kidney function indexes in mild and severe COVID-19 patients and their capability to predict the severity of the disease. Methods The characteristics and laboratory indexes were compared between patients with different conditions. We applie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 53 publications
2
21
0
Order By: Relevance
“…These findings are in agreement with previous studies stating that liver injury occurs during highly pathogenic human coronavirus infections, moreover abnormalities in laboratory indexes of blood biochemical parameters, may be associated with the severity of multiple organ dysfunction. 14,[27][28][29] Out of 73 patients 13 patients died from SARS-CoV-2 infection having decreased PON1 activity (1.19±0.46 kU/L) as compared to survivors (1.31±0.56 kU/L) (p>0.05, data not shown). Among all variables examined, PON1 and urea were found to be associated with SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 92%
“…These findings are in agreement with previous studies stating that liver injury occurs during highly pathogenic human coronavirus infections, moreover abnormalities in laboratory indexes of blood biochemical parameters, may be associated with the severity of multiple organ dysfunction. 14,[27][28][29] Out of 73 patients 13 patients died from SARS-CoV-2 infection having decreased PON1 activity (1.19±0.46 kU/L) as compared to survivors (1.31±0.56 kU/L) (p>0.05, data not shown). Among all variables examined, PON1 and urea were found to be associated with SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 92%
“…SARS-CoV-2 can cause inflammatory injury of liver, and ALB is an important indicator reflecting the severity of liver inflammatory injury in clinic. More and more studies have found that ALB is closely related to the severity of COVID-19 patients [51], which can reflect the prognosis of patients [52]. In addition, ALB is an important index for judging nucleic acid negative within 14 days [53].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, as observed in a multicenter retrospective cohort study of 12,413 confirmed COVID-19 patients, a significant association between increased baseline BUN levels and increased risk of all-cause mortality was VEGF would be useful in the approach to the regeneration of lung tissue and treatment of lung fibrosis [2,107,112] reported [121]. A recent study of 266 COVID-19 patients reported that compared with mild cases, severe patients had higher levels of BUN, proposing that BUN could be an independent element for predicting COVID-19 severity [122]. ese studies showed that higher BUN concentrations in COVID-19 cases were associated with higher disease severity and mortality rate.…”
Section: Blood Urea Nitrogen (Bun) Mudatsir Et Al In Amentioning
confidence: 96%
“…Moreover, as observed in a multicenter retrospective cohort study of 12,413 confirmed COVID-19 patients, a significant association between increased baseline BUN levels and increased risk of all-cause mortality was reported [ 121 ]. A recent study of 266 COVID-19 patients reported that compared with mild cases, severe patients had higher levels of BUN, proposing that BUN could be an independent element for predicting COVID-19 severity [ 122 ].…”
Section: Biomarkers Associated With Covid-19 Infection and Severitymentioning
confidence: 99%